2019
DOI: 10.3847/1538-4357/ab4272
|View full text |Cite
|
Sign up to set email alerts
|

New Millimeter CO Observations of the Gas-rich Debris Disks 49 Cet and HD 32297

Abstract: Previous observations revealed the existence of CO gas at nearly protoplanetary level in several dust-rich debris disks around young A-type stars. Here we used the ALMA 7m-array to measure 13 CO and C 18 O emission toward two debris disks, 49 Cet and HD 32297, and detected similarly high CO content (>0.01 M ⊕ ). These high CO masses imply a highly efficient shielding of CO molecules against stellar and interstellar ultraviolet photons. Adapting a recent secondary gas disk model that considers both shielding by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 100 publications
3
72
4
Order By: Relevance
“…In this latter case, the model does not give us a unique answer regarding the event time, other than that it must be greater than ∼ 10 5 yr. For comparison, the system lifetime is larger than 15 Myr. The CO production rate of 15 M ⊕ Myr −1 is in contrast with the result from Moór et al (2019), where they found that P CO ≈ 3.6 × 10 −2 M ⊕ Myr −1 . However, the Moór et al (2019) model over-predicts the C 0 mass by a factor 10 compared to our data, despite underestimating the CO break-down rate due to the different treatment of shielding (section 4.1).…”
Section: Full Calculationmentioning
confidence: 58%
See 3 more Smart Citations
“…In this latter case, the model does not give us a unique answer regarding the event time, other than that it must be greater than ∼ 10 5 yr. For comparison, the system lifetime is larger than 15 Myr. The CO production rate of 15 M ⊕ Myr −1 is in contrast with the result from Moór et al (2019), where they found that P CO ≈ 3.6 × 10 −2 M ⊕ Myr −1 . However, the Moór et al (2019) model over-predicts the C 0 mass by a factor 10 compared to our data, despite underestimating the CO break-down rate due to the different treatment of shielding (section 4.1).…”
Section: Full Calculationmentioning
confidence: 58%
“…via re-capture by dust grains). The shielding aspect of our model is similar in spirit to that in Kral et al (2019); Moór et al (2019); Marino et al (2020), but differs (substantially) in the treatment of shielding.…”
Section: Time Evolution Modelmentioning
confidence: 63%
See 2 more Smart Citations
“…If we scale those thresholds by ν 2 (assuming optically thick emission) and by d 2 to account for the difference in distance to the 49 Ceti system, then our upper limits on the integrated HCO + (4-3) and HCN(4-3) flux from Ceti are about a factor of 50 below the sensitivity of theÖberg et al (2010,2011) survey. The CO(2-1) emission from 49 Ceti (3.87 ± 0.41 Jy km s −1 , Moór et al 2019) is 26 times lower than the average for the disks in theÖberg et al ( 2011) survey, and 10 times lower than the faintest disk in the survey. Looking at it another way, the ratio of HCO + /CO flux within a given band varies in theÖberg et al (2010,2011) sample between 0.11 and 0.59, while the ratio for 49 Ceti at Band 7 is < 0.006.…”
Section: Comparison With Observed Molecular Abundances Of Protoplanetary Disks and Cometsmentioning
confidence: 62%